Java in Indonesian Horor Films - Ilma Saakinah Tamsil (PERSPEKTIF, 2023)
The development of post-Covid-19 horror films has not lowered spirits the enthusiasm of Indonesian filmmakers to produce horror films that elevate Javanese culture. This article aims to explain story concepts for Javanese culture that appear in the film as something mystical from songs, spells, rituals, myths, beliefs, ancient ornaments, costumes, and the language used. This is often alluded to with the tradition of Kejawen which is mostly adhered to by the Javanese people. Kejawen emerged from the beliefs and rituals of a mixture of formal religions with the worship of natural forces. The Javanese view, society, and nature as a unity in life. Nature becomes a major determinant for the safety and destruction of life. Another belief is in kesaktén (supernatural powers), belief in ancestral spirits, and spirits are considered to be able to bring peace, and safety but also health problems, thoughts, and even death. The book Spiritualism of Java by Iman Budhi Santosa on the history, practice, and essence of Javanese teachings is used to approach this problem. Data was collected from selected horror films from 2019 to 2022 and analyzed qualitatively. This study concludes that the understanding of Kejawen is incomplete, so various traditions, rituals, and myths are based on the belief that Javanese culture is often mystical, occult, and frightening, so it is often used as an idea to attract the attention of horror film lovers.